If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -6x + 4x = -1 + -5(7 + -2x) Combine like terms: -6x + 4x = -2x 4 + -2x = -1 + -5(7 + -2x) 4 + -2x = -1 + (7 * -5 + -2x * -5) 4 + -2x = -1 + (-35 + 10x) Combine like terms: -1 + -35 = -36 4 + -2x = -36 + 10x Solving 4 + -2x = -36 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 4 + -2x + -10x = -36 + 10x + -10x Combine like terms: -2x + -10x = -12x 4 + -12x = -36 + 10x + -10x Combine like terms: 10x + -10x = 0 4 + -12x = -36 + 0 4 + -12x = -36 Add '-4' to each side of the equation. 4 + -4 + -12x = -36 + -4 Combine like terms: 4 + -4 = 0 0 + -12x = -36 + -4 -12x = -36 + -4 Combine like terms: -36 + -4 = -40 -12x = -40 Divide each side by '-12'. x = 3.333333333 Simplifying x = 3.333333333
| 126-6x=2x-22 | | 20x^2+20=41x | | -19-2x=17-7x | | .2(2x-6)=3 | | 40-8x=27+3x | | .4(2x-6)=3 | | 7-7x=9+3x | | 2x-5=12x-37 | | x^2+2x^2-9x=18 | | 3ln(x-2)=9 | | 19-(x+8)=7x+5 | | -19(x+8)=7x-5 | | -15(2a-9b+8c)= | | 7-7x=6+x | | 7x-6=-62 | | (5u-8)(4-u)=0 | | 33=-5x+3(2x+14) | | 6x-5=16x-42 | | 10X+5+2X+25=48-X+1035 | | 39-5x=2x+12 | | 4x^2-45=85 | | 3m-12=6 | | 4x-7=35 | | 1-12x=7(1-2x) | | 0=5n+2n | | -6+7x^2+6+7x=0 | | 1-12x=7-14x | | (7m+3b)(7m-3b)= | | -5g+1=q+2g | | 61.54=.61x^2-0.046x+1 | | 3x-20=40 | | 0.25y-0.2=0.15y+1-0.5y |